Patentability of Bioprinting Technology: Where Invention Meets Requirement (Journal of Intellectual Property Rights (JIPR), 2025)
With the ability to print human organs on demand, 3D bioprinting has the potential to be a "game-changer," eliminating the need for human or animal transplantation or living or deceased donor organ donation. The market of organ transplantation is mammoth, driving several companies to opt for patent protection of their bioprinting technology over other means of intellectual property. By resorting to a doctrinal study powered with deductive reasoning, the study highlights that even though clinical organ transplantation present ethical challenges, bioprinting has its own set of practical, ethical, and regulatory issues that need to be resolved. These have to do with controlling public expectations and the morality of biomedicine's continued reliance on pricey technological fixes. The legitimacy of patent monopoly by providing essential health products and services as luxury goods has come under scrutiny, particularly in Low and Middle Income Countries (LMICs), where such technologies relentlessly widen the gaps in healthcare. Put simply, usage of living cells, brings in the thought of patentability issue in relation to bioprinting technology. The purpose of this study has been to envisage a road map towards developing a viable, equitable and sustainable industry will need to strike an optimal balancebetween rights and responsibilities among different stakeholders, including governments, 3D bioprinting companies and patients (and the public).